2015
DOI: 10.1080/00981389.2015.1078427
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of opioid-dependent women in their prenatal and postpartum care: Implications for social workers in health care

Abstract: The prevalence of prescription opioid abuse has increased nationally in the last decade with increased incidence rates reported among pregnant women. This was a qualitative study designed to understand the role of pregnant women with an opioid use disorder participating in medical decision making regarding their prenatal care while addressing their addiction. Group interviews were conducted with postpartum women who self-identified as opioid dependent during their pregnancy, and the data were analyzed using In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 33 publications
0
49
0
10
Order By: Relevance
“…Pregnant women with substance use disorders are often perceived as criminals rather than individuals with a serious health condition [13], resulting in an uncertain and potentially hostile environment of care [14,15]. For many pregnant women, substance use treatment is difficult to obtain due to lack of programs willing to treat pregnant women, cost, lack of medical coverage, fear of legal consequences, and threat of child protection involvement for women who have children [16,17]. These factors intensify the stigma associated with prenatal substance use [16,[18][19][20][21] and are reinforced by social determinants, further limiting access to care [19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women with substance use disorders are often perceived as criminals rather than individuals with a serious health condition [13], resulting in an uncertain and potentially hostile environment of care [14,15]. For many pregnant women, substance use treatment is difficult to obtain due to lack of programs willing to treat pregnant women, cost, lack of medical coverage, fear of legal consequences, and threat of child protection involvement for women who have children [16,17]. These factors intensify the stigma associated with prenatal substance use [16,[18][19][20][21] and are reinforced by social determinants, further limiting access to care [19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women and postpartum women with SUDs experience stigma through judgmental attitudes expressed by health care providers. The women report that because they use substances providers undermine their decision-making, refer to them with negative labels (e.g., "methadone mom") and provide differential treatment for them, thereby the impairing formation of trust (Demirci et al, 2015;Howard, 2015;Howard, 2016;Jessup et al, 2003;Leppo, 2012). Perceived stigma has been associated with increased substance use and dissatisfaction with pregnancy (Best et al, 2014) and decreased utilization of prenatal health care (Gilchrist et al, 2012;Hall & Teijlingen, 2006).…”
Section: Substance Use and Health Care Experiences In Pregnancy And Pmentioning
confidence: 99%
“…Demirci et al, (2015) In this analysis, we describe the experiences and perceptions impacting breastfeeding decisions among pregnant and postpartum women taking methadone. (Cleveland et al, 2016;Cleveland & Bonugli, 2014;Cleveland & Gill, 2013;Howard, 2015;Howard, 2016;Jarlenski et al, 2016;Kramlich et al, 2018;McGlothen et al, 2018;Roberts & Nuru-Jeter, 2010;Roberts & Pies, 2011;Salmon et al, 2000;Scott et al, 2017;Stone 2015;Suarez et al, 2018) .53…”
Section: Semistructured Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a systematic review of collaborative chronic care models found that patients with mental health conditions who had received collaboratively-administered interventions were less depressed, had better physical quality of life and social role function than those who did not (Woltmann ALL AUTHORS ., 2012). Within such interdisciplinary care teams research has shown that social workers play a critical role in addressing the psychosocial needs of patients (Howard, 2016;Miller et al, 2007).…”
mentioning
confidence: 99%